Ongoing and emerging issues for sustainable bioenergy production on marginal lands in the Mediterranean regions - Pulighe, G.; Bonati, G.; Colangeli, M.; Morese, M.M.; Traverso, L.; Lupia, F.; Khawaja, C.; Janssen, R.; Fava, Francesco P. (Elsevier, 2019)
The cultivation of marginal lands for bioenergy production has recently become a topic of research interest for the agronomic and agricultural economy scientific communities. The growing availability of arable land in the Mediterranean regions, as a consequence of the decline of cereal cropping systems and grain legume, provides ample opportunities for performing successful feedstock production on unmanaged areas. This paper seeks to capture and analyze ongoing and emerging questions concerning bioenergy production on marginal lands in the Mediterranean area in a framework of sustainability indicators. A qualitative methodology was adopted to evaluate the effectiveness of eight critical issues that bio-energy developers, scholars and policymakers should consider in terms of agronomic, techno-economic and methodological practices for growing bioenergy feedstock. The issues investigated on selected case studies are: Greenhouse gas emissions; soil quality; land restoration and phytoremediation capacity; water use and efficiency; biodiversity; land use/cover changes; farmers’ willingness and acceptance of new agro-system, and profitability of value chain. Starting from an in-depth analysis of the definition of marginal land from the perspective of ecosystem service cascade, we synthesize how these challenges are nowadays addressed and which are the key bottlenecks, trends and potential directions for guiding future research into bioenergy production in the Mediterranean regions. The findings of this study suggest that dedicated energy crops can be grown on marginal lands with substantial positive effects in terms of sustainability aspects, although more efforts should be carried out through agronomic research especially on water use efficiency and biodiversity conservation, as well as by national and EU institutions and policies for promoting economic opportunities and integration with surrounding agro-ecosystems and farmers’ involvement. Developing a site-specific landscape design with the use of Life Cycle Assessment and certification schemes with sustainability indicators is of primary importance for the effective bioenergy production on marginal lands.